Counter-Point: Staying Honest When Policy Changes Backfire. Issue 5 (May 2018) - Lu, Christine Y.; Simon, Gregory; Soumerai, Stephen B.
Abstract : Despite the good intentions of the Food and Drug Administration (FDA), many drug warnings are ineffective or have unintended consequences, particularly if the media exaggerates the messages and scares the public. The controversial 2003 to 2004 FDA warnings on youth suicidality associated with antidepressant use are a case in point. In a 10-year interrupted time series (ITS) analysis in 11 health plans, we found that the warnings and hyped media coverage led to substantial reductions in antidepressant use (declines in antidepressant use and overall care corroborated in several studies), and small, visible increases in emergency room and inpatient poisonings with psychotropic drugs. In a gross misunderstanding of the method, Dr Stone calls ITS, "an intuition based upon false analogies, fallacious assumptions and analytical error." We demonstrate visually using published studies that the ITS method is one of the oldest (hundreds of years) and strongest quasi-experimental study designs, and that the alternative data analyses proposed by Dr Stone do not have rates (denominators), nor baselines, so the measures of change are invalid.